Biosorption Of Colour In Landfill Leachate Using Raw Hydrilla Sp. - Aminuddin, Yasmin (Universiti Sains Malaysia, 2022)
This study was conducted to investigate the performance of untreated raw Hydrilla Sp. as a new biosorbent in treating landfill leachate. Leachate water contains very high concentrations of colours and other contaminants which can affect water quality and make it unpleasant to the environment. High coloured leachate samples were obtained from the Alor Pongsu Landfill Site, Kerian, Perak, which is currently not treated. The leachate was first characterised. The Hydrilla sp was prepared by pre-washing and drying, followed by grinding into 0.7mm to 1.18mm as working sizes. The biosorbent was characterised by means of BET, XRD, FTIR, and zeta potential. Batch studies were performed at different adsorbent dosages (1g, 2g, 3g, 4g, and 5g) and pH values (pH6.76 and pH7). The adsorption was measured by a Spectrophotometer (DR 2800 HACH, USA). The results show that hydrilla contains -OH, -COOH and -NH groups which could contribute to the biosorption efficiency where the attraction electrostatic between sorbent and sorbate occurred. The result indicated that the optimal result for treating leachate occurred at 2g of Hydrilla. However, since the Hydrilla has its own colour that added to the colour in leachate, the performances were hardly evaluated with a lot of negative results. Nonetheless, the Hydrilla could be further examined in future by heat activation and carbonation to make it as an activated carbon. There is also possibility to test it for metal removals which may not be influenced by the Hydrilla colour.